Uji Aktivitas Diuretik Ekstrak Daun Matoa (Pometia pinnata) pada Tikus Jantan Galur Wistar - Ika Purwidyaningrum; Muhammad Dzakwan (Fakultas Farmasi Universitas Setia Budi, 2015)
Matoa leaves (Pometia pinnata) empirically were used as antihypertensive. Diuretic medicine correlated with antihypertensive drugs so this study aims to determine the effect of diuretics matoa leaves extract. Matoa leaves ethanol extract was tested on male rats wistar strain. Animal tests used as many as 25 tails were divided into 5 groups, namely: negative control CMC 0.5%, furosemide 3.6 mg/kg, matoa leaves ethanol extract 50 mg/kg, matoa leaves ethanol extract 100 mg/kg BB, matoa leaves ethanol extract 150 mg/kg. Then the hour urine volume is recorded at 1, 2, 3, 4, 5 and 24 hours. Diuretic effect can be seen from the analysis of data obtained diuretic percent of the volume of urine each time of observation. Results of this research was conducted matoa leaves extract diuretic test. Based on data and ANOVA test can be concluded that the ethanol extract of the matoa leaves can efficacious as a diuretic and its effective dose is 100 mg/kg.